Epitaxial synthesis of monolayer PtSe2 single crystal on MoSe2 with strong interlayer coupling - Zhou, Jiadong (2021)
PtSe2, a layered two-dimensional transition-metal dichalcogenide (TMD), has drawn intensive attention owing to its layer-dependent band structure, high air stability, and spin-layer locking effect which can be used in various applications for next-generation optoelectronic and electronic devices or catalysis applications. However, synthesis of PtSe2 is highly challenging due to the low chemical reactivity of Pt sources. Here, we report the chemical vapor deposition of monolayer PtSe2 single crystals on MoSe2. The periodic Moiré patterns from the vertically stacked heterostructure (PtSe2/MoSe2) are clearly identified via annular dark-field scanning transmission electron microscopy. First-principles calculations show a type II band alignment and reveal interface states originating from the strong-weak interlayer coupling (SWIC) between PtSe2 and MoSe2 monolayers, which is supported by the electrostatic force microscopy imaging. Ultrafast hole transfer between PtSe2 and MoSe2 monolayers is observed in the PtSe2/MoSe2 heterostructure, matching well with the theoretical results. Our study will shed light on the synthesis of Pt-based TMD heterostructures and boost the realization of SWIC-based optoelectronic devices.